A Non-Profit Case Management Model: Impact on Severely Wounded, Ill, and Injured Service Members and Veteran Well-Being - Gregory J Hamilton; Vanessa M Rivera; Jeannie L Bay; Michael T Fredericks; Jeff B Clark (Military Medicine, 2026)
Abstract Introduction Long-term care for our nation’s severely wounded, ill, and injured service members and veterans (SM/Vs) and their families presents formidable challenges. Besides physical trauma, conditions like traumatic brain injury and post-traumatic stress disorder require sustained, lifelong support. While federal systems provide acute and rehabilitative care, gaps may emerge in managing the chronic and social complexities of recovery. Semper Fi & America’s Fund (The Fund), a 501(c)(3) non-profit organization, developed a unique model of lifelong case management and supportive services that provides a continuous, personal relationship to severely injured SM/V. Evidence of The Fund’s positive impact on SM/V well-being has so far been anecdotal; this study sought to examine it objectively. Materials and Methods This retrospective cohort study used a Fund-provided deidentified, binomial data set from 289,160 case manager notes covering 2 decades associated with 18,425 severely wounded, ill, and injured Operation Enduring Freedom and Operation Iraqi Freedom SM/Vs. The Fund did not provide the actual notes; but rather provided text-mined anonymized data in a binary format for the presence of 4 well-being challenges: anxiety, suicidal ideation, legal issues, and substance use. The SM/Vs were divided into groups based on when they joined The Fund. Unadjusted odds ratios were used to assess the effect of length of exposure to the case management model on each of the challenges. Results The SM/Vs with the least amount of exposure to the case management model were statistically (P < .0001) more likely to have each of the challenges documented in their case manager notes: anxiety (OR 5.64-13.22); suicidal ideation (OR 2.84-4.84); legal issues (OR 3.10-5.10); and substance use (OR 5.19-7.46). Conclusion This is the first study reported in the literature that used a large 20-year database of case manager data. The results suggest that a proactive, relationship-based, and lifelong case management model may improve well-being outcomes for severely wounded, ill, and injured SM/Vs. Specifically, longer exposure to The Fund’s model may improve SM/V well-being for each of the studied challenges. Future research and data analysis could help government and nonprofit agencies best allocate resources to meet the needs of severely wounded, ill, and injured SM/Vs in future conflicts.